High mobility group box 1 contributes to wound healing induced by inhibition of dipeptidylpeptidase 4 in cultured keratinocytes - Sinagra, Tiziana; Merlo, Sara; Spampinato, Simona F.; Pasquale, Rocco De; Sortino, Maria Angela (Frontiers in Pharmacology, 2015)
Dipeptidyl peptidase 4 (DPP4) is expressed in various tissues, including the skin, and DPP4 inhibitors, that are currently used for the treatment of diabetes, may be effective also for complications of diabetes that affect the skin. To assess the role of DPP4 in keratinocytes, after creating a scratch wound in a monolayer of NTCC 2544 cells, we evaluated DPP4 expression and monitored wound repair over time, after treatment with the DPP4 inhibitor 1(((1-(hydroxymethyl)cyclopentyl)amino)acetyl)2,5-cis-pyrrolidinedicarbonitrile (DPP4-In). Expression of DPP4 increased early and was maintained up to 48 h following the scratch as shown by western blot and immunostaining. Treatment with 10 μM DPP4-In reduced DPP4 expression and significantly accelerated wound repair. This effect did not involve enhanced cell proliferation as shown by MTT proliferation assay, the lack of changes of cell cycle profiles and the slight inhibition of ERK phosphorylation. Enhancement of wound repair by DPP4 inhibition was prevented by the non specific MMPs inhibitor GM6100 (5 μM). Treatment with DPP4-In increased the expression of high mobility group box 1 (HMGB1), a substrate of this enzyme, and exposure of NCTC 2544 cells to DPP4-In and exogenous HMGB1 (10 nM) produced a non additive effect. Finally the healing promoting effect of DPP4-In was prevented by pretreatment with a neutralizing anti-HMGB1 antibody. The present results suggest that DPP4 inhibition contributes to enhanced wound healing by inducing keratinocytes to migrate into a scratched area. This effect seems to be independent of cell proliferation and involves enhanced production of HMGB1.